WARUNG KOPI SEBAGAI SARANA KOMUNIKASI DAN SUMBER INFORMASI BAGI PROFESI WARTAWAN DI KOTA PADANG - Putra, Tri Hikmahdi (Menara Ilmu, 2017)
This study discusses the "Coffee Shop as Communication Media and as a Place for Source of Information for Journalists in Padang," This study used a qualitative study with approach of empirical phenomena of the coffee shop for the journalistic profession in Warung Kopi Kubik Coffe, Warung Coffee KPU and Coffee Shops Tan Malaka in the city of Padang. The purpose of this study was to determine the motives behind the presence of reporters in a coffee shop, to knowing the function and role of coffe shop for journalists, and know the meaning and role of the coffee shop as a means of journalistic profession. The theories used as a guideline in this study is the Social Construction, Phenomenology, Social Communication Between Personal, Facts, Mass Media, News, Reporters and audiences constructionist views of Paradigm and professionalism of journalists. As for the informants in this study is as much as ten journalists. Data collection techniques in this research is in-depth interviews, direct observation and documentation, while the categorization data analysis techniques using data reduction, narrating of data, interpretation of data, drawing conclusions, and verification of data. The results showed that the coffee shop as a social reality with a wide range of facilities provided in a coffee shop interpreted as a means of communication and source of information for the journalistic profession in padang city. The existence of a coffee shop as a public space has now been made the reporters get information and more accurate. The coffee shop as a public space for journalists can serve as a meeting place of the community and the level below the top level. The coffee shop as a public space in the city field is basically an attempt to meet the needs of modern public space. Coffee shop not only as a place to meet the need for consumption of coffee, relax, be entertained and relax, but had become a public space that can open up opportunities for people to discuss social issues freely and openly in coffee shops. Keywords : Journalist, Coffee Shops, Communication Media, Information Resources, Free Wi-Fi, Public Space